2022
DOI: 10.17159/2224-7912/2018/v58n1a3
|View full text |Cite
|
Sign up to set email alerts
|

Dagloners: 'n Gevallestudie van die kwesbaarheid van die maatskaplike bestel en samehorigheid in Suid-Afrika se informele ekonomie

Abstract: is tans professor en gegradeerde navorser in die Departement Maatskaplike Werk aan die Universiteit van die Wes-Kaap (UWK). Voordat sy by UWK begin werk het, was sy 25 jaar aan Unisa en 6 jaar aan die Universiteit van Pretoria (UP) verbonde. Haar navorsing is gerig op armoede, werkloosheid en in besonder op die persone wat 'n bestaan probeer maak in die informele ekonomie. Professor Schenck en haar navorsingspan gee veral aandag aan die dagloners en vullisherwinners. Sy het reeds wyd in nasionale en internasio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The effects of the disrupted lives of families that the literature reveals have extremely adverse consequences for the lives of both day labourers and their families (Xweso 2019;Mapandere et al 2019). Schenck and Blaauw (2018) contend that the social fabric of the families of day labourers is subjected to tremendous pressure and sometimes unravels. They found that 26 percent of the day labourers in their research sample were married with children and did not earn sufficient income from their daily work to afford to take care of themselves and their dependants.…”
Section: Dislocated Family Lives Of Day Labourersmentioning
confidence: 99%
“…The effects of the disrupted lives of families that the literature reveals have extremely adverse consequences for the lives of both day labourers and their families (Xweso 2019;Mapandere et al 2019). Schenck and Blaauw (2018) contend that the social fabric of the families of day labourers is subjected to tremendous pressure and sometimes unravels. They found that 26 percent of the day labourers in their research sample were married with children and did not earn sufficient income from their daily work to afford to take care of themselves and their dependants.…”
Section: Dislocated Family Lives Of Day Labourersmentioning
confidence: 99%